The regulation of slyA gene expression in phytopathogenic bacteria Erwinia amylovora - Pesotskaya, Karina Yu.; Sorokin, Dmitry V.; Lagonenko, Alexander L.; Evtushenkov, Anatoli N. (Experimental Biology and Biotechnology, 2026)
The work investigated the effect of compounds of different chemical nature on the activity of the promoter of the transcriptional regulator SlyA. As a result, it was found that hydrogen peroxide and polymyxin B induce slyA gene expression. It was also noted that the SlyA protein activates the transcription of the slyA, yhcN and ohrA genes. It was concluded that the tested plant phenolic compounds (salicylic, chlorogenic, vanillic, caffeic, cinnamic, p-hydroxybenzoic and ferulic acids) in physiological concentrations do not regulate slyA gene expression.
Keywords: Erwinia amylovora; SlyA regulator; plant phenolic compounds; polymyxin B; hydrogen peroxide; gene expression